A treatment protocol to guide the delivery of dialogical engagement with auditory hallucinations: Experience from the Talking With Voices pilot trial. (25th February 2021) - Longden, Eleanor; Corstens, Dirk; Morrison, Anthony P.; Larkin, Amanda; Murphy, Elizabeth; Holden, Natasha; Steele, Ann; Branitsky, Alison; Bowe, Samantha
Abstract : Purpose: To present a treatment protocol for delivering Talking With Voices, a novel intervention for people with psychosis that involves dialogical engagement with auditory hallucinations. Method: This paper presents a manualized approach to therapy employed in the Talking With Voices trial, a feasibility and acceptability randomized control trial of 50 adult participants. A rationale for following a treatment manual is provided, followed by the theoretical underpinnings of the intervention and its principles and values, including the main tenet that voices can often be understood as dissociated parts of the self which serve a protective function by indicating social–emotional vulnerabilities. The four therapy phases for improving the relationship between the voice‐hearer and their voices are outlined: (1) engagement and psychoeducation, (2) creating a formulation, (3) dialoguing with voices, and (4) consolidating outcomes, including key milestones at each phase. Implementation issues are discussed, as well as recommendations for best practice and future research. Results: The Talking With Voices treatment protocol indicates that it is feasible to manualize a dissociation‐based approach to support service users who are distressed by hearing voices. Conclusion: For some individuals, it is possible to engage in productive dialogue with even extremely hostile or distressing voices. Developing coping strategies, creating a formulation, and ultimately establishing a dialogue with voices has the potential to improve the relationship between voice(s) and voice‐hearer. Further research is now required to evaluate feasibility, acceptability, and efficacy. Practitioner points: It is feasible to integrate a dissociation model of voice‐hearing within a psychological intervention for people with psychosis. Combining psychosocial education, formulation and direct dialogue can be used to facilitate a more peaceful relationship between clients and their voices. Practitioners trained in other therapeutic modalities can draw on existing transferrable skills to dialogue with their clients' voices. The input of those with lived experience of mental health difficulties has an important role in guiding treatment design and delivery.